Optimizing the synthesis of CdS/ZnS core/shell semiconductor nanocrystals for bioimaging applications - Liu, Li-wei; Hu, Si-yi; Pan, Ying; Zhang, Jia-qi; Feng, Yue-shu; Zhang, Xi-he (Beilstein Journal of Nanotechnology, 2014)
In this study, we report on CdS/ZnS nanocrystals as a luminescence probe for bioimaging applications. CdS nanocrystals capped with a ZnS shell had enhanced luminescence intensity, stronger stability and exhibited a longer lifetime compared to uncapped CdS. The CdS/ZnS nanocrystals were stabilized in Pluronic F127 block copolymer micelles, offering an optically and colloidally stable contrast agents for in vitro and in vivo imaging. Photostability test exhibited that the ZnS protective shell not only enhances the brightness of the QDs but also improves their stability in a biological environment. An in-vivo imaging study showed that F127-CdS/ZnS micelles had strong luminescence. These results suggest that these nanoparticles have significant advantages for bioimaging applications and may offer a new direction for the early detection of cancer in humans.
Keywords: bioimaging; CdS/ZnS quantum dots; Pluronic F127